Two-dimensional coherent electronic spectrometer with switchable multi-color configurations [research data] - Kefer, Oskar; Kolesnichenko, Pavel V.; Buckup, Tiago (Universität, 2024)
Broadband implementation of two-dimensional electronic spectroscopy (2DES) is a desirable goal for numerous research groups, yet achieving it presents considerable challenges. An effective strategy to mitigate these challenges is the utilization of two-color approaches, effectively broadening the spectral bandwidth accessible with 2DES. Here, we present a simple approach to include multi-color configurations based on adjustable mirror mounts. This enables seamless toggling between single-color, two-color, and transient 2DES within the same spectroscopic apparatus, which is benchmarked on two common laser dyes, Rhodamine 6G and Nile blue. Upon mixing the dyes, single-color 2DES shows overlapping signals, whereas a high selectivity toward Nile blue responses is maintained in two-color and transient 2DES, owing to the fully resonant excitation that is spectrally shifted relative to the detection window. This method is readily implemented in other setups with similar experimental layouts and can be used as a simple solution to overcome existing bandwidth limitations. With the inclusion of transient 2DES, additional insights into excited-state processes can be gained due to its increased sensitivity toward excited-state coherences.
Gefördert durch: Deutsche Forschungsgemeinschaft (DFG): SFB 1249
Gesehen am 18.03.2024
Keywords: Forschungsdaten; Datenbank